How GRDP and Inflation Affect Unemployment in Lampung Province 2013 – 2024 - Khoirina, Siti; Hairudin, Hairudin; Salma, Nur; Loliyani, Rini; Loliyana, Rina (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2025)
Unemployment is one of the problems often faced by developing countries, including Indonesia. As population growth increases and the number of the Indonesian workforce increases, unemployment also continues to increase. Unemployment in Indonesia is a significant problem, as the unemployment rate increases every year, accompanied by a rise in population. Economic indicators that affect the unemployment rate. Economic growth in Indonesia, the inflation rate, and the prevailing wage rate. The indicators used in this study are GRDP, ADHB, inflation and unemployment. This study aims to analyse the influence of GRDP, ADHB, and inflation on open unemployment in Lampung Province for the period 2013-2024, both partially and simultaneously. The type of data used in this study is secondary time series data spanning the period from 2013 to 2024. The data used is data obtained from the official website of the Central Statistics Agency (BPS) of Lampung Province. The analysis method employed in this study is multiple linear regression analysis, utilising SPSS 26 software. The results of the study indicate that Gross Real Domestic Product (GRDP) has a negative and statistically significant influence on open unemployment in Lampung Province from 2013 to 2024, with a probability value of -1.725. Simultaneously, GRDP and inflation variables have a significant impact on unemployment in Lampung Province from 2013 to 2024. The R test result value is 52.9% and the remaining 47.1% is influenced by other factors not examined in this study.